2021
DOI: 10.3389/fnagi.2020.621298
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte and NK Cell Counts Can Predict Sepsis-Associated Delirium in Elderly Patients

Abstract: Background: Sepsis-associated delirium (SAD) is prevalent in elderly patients and is recognized as brain dysfunction associated with increased inflammatory response in the central nervous system during sepsis. Neuroinflammation was demonstrated to be part of its mechanism and we aimed to validate the role of immunity imbalance in a combined retrospective and prospective cohort study.Methods: We performed a retrospective study analyzing the association between SAD and lymphocyte counts in the peripheral blood, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…The median age of the patients was 72 years (interquartile range: 68–78 years) and 62.1% (157/253) were men. At admission to the ICU, the mean SOFA score was 11.49 ± 3.95, the median APACHE II score was 18 ( 12 18 ), and the median CPIS score was 6 ( 5 8 ). Ninety-two (36.4%) patients had heart failure, 19 (7.5%) had chronic obstructive pulmonary disease, 74 (29.2%) had diabetes mellitus, 3 (1.2%) had liver cirrhosis, 44(17.4%) with tumors, and 18 (7.1%) had chronic renal failure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median age of the patients was 72 years (interquartile range: 68–78 years) and 62.1% (157/253) were men. At admission to the ICU, the mean SOFA score was 11.49 ± 3.95, the median APACHE II score was 18 ( 12 18 ), and the median CPIS score was 6 ( 5 8 ). Ninety-two (36.4%) patients had heart failure, 19 (7.5%) had chronic obstructive pulmonary disease, 74 (29.2%) had diabetes mellitus, 3 (1.2%) had liver cirrhosis, 44(17.4%) with tumors, and 18 (7.1%) had chronic renal failure.…”
Section: Resultsmentioning
confidence: 99%
“…In this nurse-led GDLPT study, pain assessment, delirium assessment, and active early activities were carried out every 6 h by nurses. Delirium varies from 11 to 42% in older patients and has adverse outcomes and high health care costs ( 18 ). Up to 60% of delirious patients were unrecognized unless actively screened, and sedative medications and deeper sedation are associated with the development of delirium ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dongkai Li et al. reported that lymphocyte and NK cell counts were significantly higher in senior patients with SAD, and NK cell count may be valuable for the prediction of SAD within elderly patient cohorts ( 34 ). In our study, we demonstrated that CD14 hi CD16 — monocytes were significantly downregulated in patients with SAD.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood samples were collected by PUMCH laboratories at enrollment with EDTA anticoagulant for measurement of lymphocyte counts and immunological biomarkers, as described previously ( Li D. et al, 2020 ). Peripheral blood mononuclear cells were separated, stained with fluorescent monoclonal antibodies, and underwent flow cytometric analysis (3-color EPICSXL flow cytometer; Beckman Coulter, Brea, CA, United States) to detect T cells (CD3 + ), CD4 + T cells (CD4 + CD3 + and CD28 + CD4 + ), CD8 + T cells (CD8 + CD3 + , CD28 + CD8 + ), B cells (CD19 + ), and natural killer cells (CD3 – CD16 + CD56 + ).…”
Section: Methodsmentioning
confidence: 99%